High-strength steel plates and automobile bodies
Patent Information
- Application Number
- JP2022056742
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-30
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2042-03-30
AI Technical Summary
【0012】 本発明の高強度鋼板は、遅れ破壊が効果的に抑制される優れた耐遅れ破壊性を有するとともに、優れた耐食性を有する。本発明の高強度鋼板は、自動車、建材用の強度部材に好適に用いられる。特に、自動車車体の中で、高強度が必要とされ、かつ、腐食環境が厳しいサイドシル、センターピラー下部、バンパー等の自動車車体の下部構造部材やロアアーム等の自動車車台(シャシー)構造部材に好適に用いることが出来る
Smart Images

Figure 0007632372000003 
Figure 0007632372000004 
Figure 0007632372000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength steel plate, in particular to a high-strength steel plate excellent in delayed fracture resistance, and more specifically to a high-strength steel plate which is suitable mainly for strength members for automobiles and building materials, has excellent delayed fracture resistance and corrosion resistance, and preferably has a tensile strength of 1180 MPa or more. [Background technology]
[0002] Conventionally, galvanized steel sheets have been widely used as steel sheets for automobiles. This is because the sacrificial anticorrosive effect of zinc can significantly improve the corrosion resistance of steel sheets after painting. In recent years, efforts have been made to increase the strength of steel sheets for automobiles from the perspective of reducing CO2 emissions from automobiles and ensuring safety.
[0003] However, it is known that increasing the strength of steel makes it more susceptible to a phenomenon called delayed fracture. This delayed fracture becomes more likely as the strength of the steel increases, and is particularly noticeable in high-strength steel with a tensile strength of 1180 MPa or more. Delayed fracture is a phenomenon in which high-strength steel is subjected to a static load stress (load stress less than the tensile strength) and, after a certain amount of time has passed, suddenly undergoes brittle fracture with little or no apparent plastic deformation.
[0004] It is known that this delayed fracture occurs in the case of steel sheets due to residual stresses generated when the steel sheets are pressed into a predetermined shape and hydrogen embrittlement of the steel sheets at the stress concentration points. The hydrogen that causes this hydrogen embrittlement is considered to be hydrogen that penetrates into the steel sheets from the external environment and diffuses therein. Typically, hydrogen that is generated during corrosion of the steel sheets penetrates into the steel sheets and diffuses therein. In general, galvanized steel sheets penetrate more hydrogen during corrosion than cold-rolled steel sheets, and are exposed to a more severe environment for the occurrence of delayed fracture. In particular, among automotive structural components, the lower structural components of the automobile body, such as the side sills (rockers), lower parts of the center pillars (B-pillars), and bumpers, as well as the structural components of the automobile chassis, such as the lower arms, are in a severe corrosive environment and are particularly required to take measures to prevent delayed fracture.
[0005] In order to prevent such delayed fracture in high-strength steel sheets, for example, Patent Document 1 studies reducing the delayed fracture susceptibility by adjusting the structure and components of the steel sheet, while Patent Document 2 studies high-strength hot-dip galvanized steel sheets that prevent delayed fracture. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2004-231992 A [Patent Document 2] Japanese Patent Application Publication No. 6-145893 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the technology disclosed in Patent Document 1 does not change the amount of hydrogen that penetrates into the steel sheet from the external environment, so although it can delay the occurrence of delayed fracture, it cannot prevent delayed fracture itself. Furthermore, even if the steel composition and microstructural structure are adjusted based on the technology disclosed in Patent Document 2, further improvement in delayed fracture resistance has been desired.
[0008] Therefore, a high strength steel plate having both excellent corrosion resistance and delayed fracture resistance has not yet been put to practical use.
[0009] An object of the present invention is to solve the above-mentioned problems of the prior art and to provide a high-strength steel sheet excellent in delayed fracture resistance and corrosion resistance suitable mainly for strength members for automobiles and building materials. [Means for solving the problem]
[0010] In order to solve the above problems, the present inventors have conducted extensive research and studies into means for preventing delayed fracture by suppressing hydrogen penetration into the steel sheet. As a result, they have found that by coating the surface of a base steel sheet with a Zn-Ni-SiO2 composite plating layer having a specific coating amount and specific Ni and SiO2 concentrations, it is possible to significantly suppress hydrogen penetration into the steel sheet, prevent delayed fracture of the steel sheet, and also obtain excellent corrosion resistance.
[0011] The present invention has been made based on these findings, and has the following gist. [1] A steel sheet having a tensile strength of 1180 MPa or more and a Zn-Ni-SiO2 composite plating layer coated on the surface of the steel sheet, The Zn-Ni-SiO2 composite plating layer has a coating weight of 0.10 g / m 2 That's all. The Ni concentration in the Zn-Ni-SiO2 composite plating layer is 2% by mass or more and less than 50% by mass, and a SiO2 concentration in the Zn-Ni-SiO2 composite plating layer is 0.1 mass% or more and less than 10 mass%. [2] The coating weight of the Zn-Ni-SiO2 composite plating layer is 20 g / m 2 The high strength steel plate according to [1], characterized in that [3] The high-strength steel plate according to [1] or [2], characterized in that the Ni concentration is 10 mass% or more and less than 30 mass%. [4] The high-strength steel plate according to any one of [1] to [3], characterized in that the SiO2 concentration is 0.5 mass % or more and less than 5 mass %. [5] The coating weight of the Zn-Ni-SiO2 composite plating layer is 90 g / m 2 The high strength steel plate according to any one of [1] to [4], wherein the strength is less than or equal to 100%. [6] The high-strength steel plate according to any one of [1] to [5], characterized in that the base steel plate has a composition containing, by mass%, C: 0.03% or more and 0.45% or less, Si: 0.01% or more and 3.00% or less, Mn: 0.5% or more and 3.5% or less, P: 0.050% or less, S: 0.0050% or less, Al: 0.001% or more and 1.500% or less, and N: 0.0100% or less, with the balance being Fe and unavoidable impurities. [7] The high-strength steel plate according to [6], characterized in that the base steel plate further contains, by mass%, one or more selected from Cu: 1.000% or less, B: 0.0050% or less, Nb: 0.100% or less, Ti: 0.200% or less, V: 0.500% or less, Mo: 1.000% or less, Cr: 1.000% or less, Ni: 1.00% or less, W: 0.200% or less, Zr: 0.200% or less, Hf: 0.200% or less, Co: 0.500% or less, Ca: 0.0050% or less, Mg: 0.0100% or less, Sn: 0.200% or less, Sb: 0.200% or less, and REM: 0.005% or less. [8] An automobile body or automobile suspension part using the high-strength steel plate according to any one of [1] to [7]. [9] An automobile body using the high-strength steel plate according to any one of [1] to [7] in one or more locations of a side sill, a lower part of a center pillar, and a bumper.
[10] An automobile chassis using the high-strength steel plate according to any one of [1] to [7] in a lower arm portion. Effect of the Invention
[0012] The high-strength steel plate of the present invention has excellent delayed fracture resistance, which effectively suppresses delayed fracture, and also has excellent corrosion resistance. The high-strength steel plate of the present invention is suitable for use in strength members for automobiles and building materials. In particular, it can be suitable for use in automobile body lower structural members such as side sills, lower center pillars, and bumpers, which require high strength and are subject to severe corrosive environments, and automobile chassis structural members such as lower arms. [Brief description of the drawings]
[0013] [Figure 1] 1 is a diagram showing a schematic diagram of a test piece for evaluating delayed fracture used in Examples. [Diagram 2] FIG. 2 is an explanatory diagram showing the steps of a combined cycle corrosion test carried out in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The high-strength steel sheet of the present invention has a substrate steel sheet having a tensile strength of 1180 MPa or more and a Zn-Ni-SiO2 composite plating layer coated on the surface of the substrate steel sheet, and the Zn-Ni-SiO2 composite coating amount is 0.10 g / m 2 The Zn-Ni-SiO2 composite plating layer is characterized by having an Ni concentration of 2 mass% or more and less than 50 mass%, and an SiO2 concentration of 0.1 mass% or more and less than 10 mass%, and has excellent delayed fracture resistance and corrosion resistance.
[0015] The steel sheet (base steel sheet) that serves as the substrate of the high strength steel sheet of the present invention is a steel sheet having a tensile strength of 1180 MPa or more, preferably 1320 MPa or more. Delayed fracture occurs when hydrogen that has penetrated into steel diffuses or concentrates in the stress concentration area, causing embrittlement, and so depends on the strength of the steel. That is, delayed fracture is essentially unlikely to occur in steel plates with low tensile strength. Thus, the effects of the present invention can be obtained with steel plates with low tensile strength, but are more pronounced in steel plates with tensile strengths of 1180 MPa or more, and more pronounced in steel plates with tensile strengths of 1320 MPa or more.
[0016] Automobile body lower structural components such as side sills, lower center pillars, and bumpers, and automobile chassis structural components such as lower arms are required to have a tensile strength of 1180 MPa or more in order to ensure high collision safety and a lightweight structure. In addition, the corrosive environment of the lower structures is such that mud and salt water accumulate as the vehicle travels, and corrosion easily progresses, so the lower structures require superior corrosion resistance compared to the upper structures of the automobile body.
[0017] The tensile strength can be measured in accordance with JIS Z 2241 (2011).
[0018] The composition and structure of the base steel sheet are not particularly limited. The rolling method is also not particularly limited, and either a hot-rolled steel sheet or a cold-rolled steel sheet may be used as the base steel sheet. Among these, it is preferable to use a cold-rolled steel sheet, considering that the steel sheet is used in the automotive field and the building material field, and is particularly used in the automotive field. That is, the base steel sheet of the present invention is preferably a high-strength cold-rolled steel sheet having a tensile strength of 1180 MPa or more, and more preferably a high-strength cold-rolled steel sheet having a tensile strength of 1320 MPa or more.
[0019] The base steel sheet preferably used in the present invention may have any chemical composition and steel structure as long as it has the desired tensile strength. In order to improve various properties such as mechanical properties, for example, structural or structural modifications such as solid solution strengthening by the addition of interstitial solid solution elements such as C and N, or substitutional solid solution elements such as Si, Mn, P, and Cr, precipitation strengthening by carbonitrides such as Ti, Nb, V, and Al, chemical composition modification such as the addition of strengthening elements such as W, Zr, Hf, Co, B, Cu, and rare earth elements, strengthening by recovery annealing at a temperature at which recrystallization does not occur or partial recrystallization strengthening in which no recrystallization occurs and an unrecrystallized region remains without complete recrystallization, strengthening by transformed structure such as single phase bainite or martensite, or a composite structure of ferrite and these transformed structures, grain refinement strengthening represented by the Hall-Petch equation: σ=σ0+kd-1 / 2 (where σ is stress, σ0, and k are material constants) where d is the ferrite grain size, and working strengthening by rolling or the like may be performed alone or in combination.
[0020] The chemical composition of such a base steel sheet may, for example, include, in mass%, C: 0.03% or more and 0.45% or less, Si: 0.01% or more and 3.00% or less, Mn: 0.5% or more and 3.5% or less, P: 0.050% or less, S: 0.0050% or less, Al: 0.001% or more and 1.500% or less, and N: 0.0100% or less, and further, in mass%, Cu: 1.000% or less, B: 0.0050% or less, Nb: 0.100% or less, Ti: 0.200% or less, and V: 0.500%. The composition may contain one or more selected from the following: Mo: 1.000% or less, Cr: 1.000% or less, Ni: 1.00% or less, W: 0.200% or less, Zr: 0.200% or less, Hf: 0.200% or less, Co: 0.500% or less, Ca: 0.0050% or less, Mg: 0.0100% or less, Sn: 0.200% or less, Sb: 0.200% or less, REM: 0.0050% or less, with the balance being Fe and unavoidable impurities. Note that P, S, and N may exceed 0% due to production technology constraints.
[0021] The chemical composition of the steel sheet of the present invention will be described below. Note that % indications regarding the components refer to mass % unless otherwise specified.
[0022] C: 0.03% or more and 0.45% or less C has the effect of increasing the strength of steel sheets. To obtain this effect, 0.03% or more of C is preferable. On the other hand, if the C content exceeds 0.45%, the weldability, which is necessary for use as a material for automobiles and home appliances, deteriorates. Therefore, the C content may be 0.03 to 0.45%.
[0023] Si: 0.01% or more and 3.00% or less Silicon is an effective element for strengthening steel and improving ductility, and to obtain this effect, 0.01% or more of silicon is preferable. On the other hand, if the silicon content exceeds 3.00%, silicon forms an oxide on the surface, which deteriorates the appearance of the plating. Therefore, the silicon content may be 0.01% or more and 3.00% or less. More preferably, it is 0.01% or more and 2.00% or less.
[0024] Mn: 0.5% or more and 3.5% or less Mn is a useful element for improving hardenability and strength of steel sheet. This effect cannot be obtained if the Mn content is less than 0.5%. On the other hand, if the Mn content exceeds 3.0%, segregation of Mn occurs and workability is reduced. Therefore, the Mn content may be set to 0.5% or more and 3.5% or less. From the viewpoint of improving workability, Mn is preferably set to 3.0% or less.
[0025] P:0.050% or less P is one of the elements that is inevitably contained, and since there is a concern of an increase in costs in order to make it less than 0.005%, it is preferable that the P content is 0.005% or more. On the other hand, if the P content exceeds 0.050%, the delayed fracture resistance of the steel sheet after forming is deteriorated through deterioration of local ductility due to grain boundary embrittlement caused by P segregation to the austenite grain boundaries during casting. Therefore, it is preferable to reduce the P content as much as possible, and the P content may be 0.050% or less. The P content is preferably 0.020% or less.
[0026] S: 0.0050% or less S is an element that is inevitably contained during the steelmaking process. However, if a large amount is contained, weldability deteriorates. Therefore, the S content may be 0.0050% or less. From the viewpoint of improving delayed fracture resistance, S is preferably 0.0020% or less. Since there is a concern that increasing costs will occur in order to reduce S to 0.0001% or less, it is preferable that S is 0.0002% or more.
[0027] Al: 0.001% or more and 1.500% or less Al is added for the purpose of deoxidizing molten steel, but if the content is less than 0.001%, this purpose is not achieved. On the other hand, if the Al content exceeds 1.500%, Al and N combine to form nitrides. The nitrides precipitate on the austenite grain boundaries during casting, causing grain boundary embrittlement and deteriorating delayed fracture resistance. Therefore, the Al content may be 0.001 to 1.500%.
[0028] N: 0.0100% or less N combines with Al to form nitrides. Nitrides precipitate on the austenite grain boundaries during casting, causing embrittlement and deteriorating delayed fracture resistance. Therefore, the N content is set to 0.0100% or less. From the above perspective, N is preferably set to 0.0050% or less. Reducing N to 0.0001% or less would be costly, so it is preferable that it is 0.0005% or more.
[0029] Cu:1.000% or less Cu has the effect of suppressing the dissolution of steel sheet in a corrosive environment and reducing the amount of hydrogen that penetrates into the steel. On the other hand, if the Cu content exceeds 1.00%, the cost increases. Therefore, the Cu content may be 1.000% or less. To obtain the above effect, the Cu content is preferably 0.005% or more.
[0030] B: 0.0050% or less The addition of B has the effect of promoting hardening. On the other hand, if the B content exceeds 0.0050%, the inclusions increase and the delayed fracture resistance deteriorates. Therefore, the B content should be 0.0050% or less.
[0031] Nb: 0.100% or less At 0.005% or more, Nb has the effect of improving strength. On the other hand, if the Nb content exceeds 0.100%, the cost increases. Therefore, when Nb is contained, the Nb content may be 100% or less, and is preferably 0.005% or more. From the viewpoint of reducing inclusions, it is more preferable that the Nb content is 0.050% or less.
[0032] Ti:0.200% or less When Ti is 0.005% or more, the effect of improving strength can be obtained. On the other hand, when the Ti content exceeds 0.200%, inclusions increase and delayed fracture resistance deteriorates. Therefore, when Ti is contained, the Ti content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, Ti is more preferably 0.080% or less.
[0033] V:0.500% or less Fine carbides formed by combining V and C are effective in improving delayed fracture resistance because they act as precipitation strengthening and hydrogen trapping sites for the steel sheet, and may be contained as necessary. If the V content exceeds 0.500 mass%, excessive carbides may precipitate, which may deteriorate the strength-ductility balance. For this reason, the V content is preferably 0.500% or less. More preferably, it is 0.100% or less, and even more preferably, it is 0.050% or less. In the present invention, in order to obtain the above effects, it is preferable that the V content is 0.005% or more.
[0034] Mo: 1.000% or less Mo has the effect of improving strength when it is 0.05% or more. On the other hand, if the Mo content exceeds 1.000%, the cost increases. Therefore, when Mo is contained, the Mo content may be 1.000% or less, and preferably 0.005% or more.
[0035] Cr:1.000% or less Cr of 0.005% or more provides a hardenability effect. On the other hand, if the Cr content exceeds 1.000%, Cr is concentrated on the surface, which deteriorates weldability. Therefore, if Cr is contained, the Cr content may be 1.000% or less, and preferably 0.005% or more.
[0036] Ni: 1.000% or less Ni content of 0.005% or more has the effect of promoting the formation of the residual γ phase. On the other hand, Ni content exceeding 1.000% leads to an increase in costs. Therefore, when Ni is contained, the Ni content may be 1.000% or less, and is preferably 0.005% or more.
[0037] W: 0.200% or less When W is 0.005% or more, the effect of improving strength can be obtained. On the other hand, when the W content exceeds 0.200%, the inclusions increase, deteriorating the delayed fracture resistance property and inviting an increase in cost. Therefore, when W is contained, the W content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, it is more preferable that W is 0.030% or less.
[0038] Zr: 0.200% or less When Zr is 0.005% or more, the effect of improving strength can be obtained. On the other hand, when the Zr content exceeds 0.200%, the inclusions increase, deteriorating the delayed fracture resistance property and inviting an increase in cost. Therefore, when Zr is contained, the Zr content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, it is more preferable that the Zr content is 0.030% or less.
[0039] Hf: 0.200% or less When Hf is 0.005% or more, the effect of improving strength can be obtained. On the other hand, when the Hf content exceeds 0.200%, the inclusions increase, deteriorating the delayed fracture resistance property and inviting an increase in cost. Therefore, when Hf is contained, the Hf content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, it is more preferable that the Hf content is 0.030% or less.
[0040] Co:0.500% or less Co has the effect of improving ductility when it is 0.005% or more. On the other hand, if the Co content exceeds 0.500%, the cost increases significantly. Therefore, if Co is contained, the Co content may be 0.500% or less, and is preferably 0.005% or more.
[0041] Ca: 0.005% or less Ca content of 0.0002% or more has the effect of spheroidizing inclusions and improving delayed fracture resistance. On the other hand, if the Ca content exceeds 0.0050%, the inclusions increase, deteriorating delayed fracture resistance and increasing costs. Therefore, if Ca is contained, the Ca content may be 0.0050% or less, and preferably 0.0002% or more.
[0042] Mg: 0.0100% or less At 0.0002% or more, Mg has the effect of spheroidizing inclusions and improving delayed fracture resistance. On the other hand, at a Mg content of more than 0.0100%, the inclusions increase, deteriorating delayed fracture resistance and increasing costs. Therefore, when Mg is contained, the Mg content may be 0.0100% or less, and preferably 0.0002% or more.
[0043] Sn: 0.200% or less At 0.002% or more, Sn has the effect of suppressing decarburization of the surface layer and improving fatigue resistance. On the other hand, at a Sn content of more than 0.200%, it embrittles the grain boundaries, deteriorating delayed fracture resistance and increasing costs. Therefore, if Sn is contained, the Sn content should be 0.200% or less, and preferably 0.002% or more.
[0044] Sb: 0.200% or less Sb has the effect of suppressing decarburization of the surface layer and improving fatigue resistance when it is 0.002% or more. On the other hand, if the Sb content exceeds 0.200%, it embrittles the grain boundaries, deteriorating delayed fracture resistance and increasing costs. Therefore, if Sb is contained, the Sb content should be 0.200% or less, and preferably 0.002% or more.
[0045] REM: 0.005% or less At 0.0002% or more, REM (Rare-Earth-Metal) has the effect of spheroidizing inclusions and improving delayed fracture resistance. On the other hand, if the REM content exceeds 0.0050%, the inclusions increase, deteriorating delayed fracture resistance and increasing costs. Therefore, if REM is contained, the REM content should be 0.0050% or less, and preferably 0.0002% or more.
[0046] The balance is Fe and unavoidable impurities.
[0047] In addition, when the content of B, Cu, Nb, Ti, Mo, Cr, Ni, W, Zr, Hf, Co, Ca, Mg, Sn, Sb, and REM described above as the preferred range of the components is less than the lower limit, the component is considered to be contained as an unavoidable impurity.
[0048] In the present invention, the thickness of the base steel sheet serving as the substrate is not particularly limited, but is preferably 0.8 to 6.0 mm, and more preferably 1.2 to 4.0 mm.
[0049] The high-strength steel sheet of the present invention is a steel sheet (base steel sheet) having a surface coated with a specific Zn-Ni-SiO2 composite plating layer, i.e., a coating amount of 0.10 g / m 2 or more, and is covered with a Zn-Ni-SiO2 composite plating layer having a Ni concentration of 2 mass % or more and less than 50 mass %, and a SiO2 concentration of 0.1 mass % or more and less than 10 mass %.
[0050] According to the results of the research and examination by the present inventors, regarding the penetration of hydrogen into the inside of zinc-plated steel sheet during the corrosion process, the inventors considered that the generation of a large amount of hydrogen on the base steel due to the sacrificial corrosion protection action of the Zn plating during the corrosion process in wet conditions is largely responsible for the delayed fracture of the steel sheet. Furthermore, they discovered that in order to suppress the penetration of hydrogen into the inside of the steel sheet, it is particularly important to suppress the penetration of hydrogen into the steel sheet during the corrosion process. They considered that in the Zn-Ni-SiO2 composite plating layer, Ni and SiO2 form corrosion products with a high corrosion suppression effect during the corrosion process, which can suppress the penetration of hydrogen into the steel sheet.
[0051] Based on the above estimated mechanism, it is considered that the coating weight of the Zn-Ni-SiO2 composite plating layer on the steel sheet surface needs to be 0.10 g / m in order to form corrosion products that are effective in suppressing hydrogen penetration. 2 It was found that the SiO2 concentration of the Zn-Ni-SiO2 composite plating layer must be 0.1 mass% or more and less than 10 mass%. In addition, when applied to members that are particularly susceptible to corrosion, the coating weight of the Zn-Ni-SiO2 composite plating layer must be 20 g / m 2 It is preferable that the amount is equal to or more than that.
[0052] The coating weight of the Zn-Ni-SiO2 composite plating layer is 0.10g / m 2If the coating weight is less than 0.10 g / m, it is not possible to achieve both sufficient hydrogen penetration suppression and corrosion resistance improvement. 2 When the coating weight of the Zn-Ni-SiO2 composite plating layer is very low, the amount of hydrogen penetration can be reduced, but the desired corrosion resistance cannot be obtained. 2 It is preferable to set the coating weight of the Zn-Ni-SiO2 composite plating layer to less than 0.10 g / m because this prevents a significant increase in manufacturing costs. 2 More than 90g / m 2 Preferably, it is less than 20 g / m 2 More than 90g / m 2 More preferably, it is less than 20 g / m 2 More than 40g / m 2 Less than 20g / m 2 More than 40g / m 2 If it is less than this, good delayed fracture resistance and corrosion resistance can be stably obtained, which is preferable.
[0053] The high-strength steel sheet of the present invention may be a steel sheet having the above-mentioned Zn-Ni-SiO2 composite plating layer coated on one side or on both sides. The coating weight of the Zn-Ni-SiO2 composite plating layer can be calculated by dissolving the Zn-Ni-SiO2 composite plating layer on the base steel sheet, and calculating the difference in mass of the steel sheet before and after dissolution.
[0054] When the Zn-Ni-SiO2 composite plating layer is applied to only one side of the base steel sheet, the above mass difference (g) should be divided by the area of one side of the base steel sheet (the above mass difference (g) / area of one side of the base steel sheet (m 2 )) can be used to measure the coverage of the Zn-Ni-SiO2 composite plating layer. In addition, when the Zn-SiO2 composite plating layer is coated on both sides of the base steel sheet, the above mass difference (g) should be divided by twice the area of one side of the base steel sheet (the above mass difference (g) / (area of one side of the base steel sheet (m 2 ) × 2)) can be used to measure the coverage of the Zn-Ni-SiO2 composite plating layer.
[0055] If the Ni concentration in the Zn-Ni-SiO2 composite plating layer is less than 2 mass% or more than 50 mass%, corrosion products with sufficient protective properties are not formed during the corrosion process, and hydrogen penetration into the steel sheet cannot be suppressed. If the SiO2 concentration is more than 10 mass%, the plating adhesion deteriorates, the plating is easily peeled off during processing, and delayed fracture resistance cannot be achieved. Therefore, the Ni concentration in the Zn-Ni-SiO2 composite plating layer must be 2 mass% or more and less than 50 mass%, and the SiO2 concentration must be 0.1 mass% or more and less than 10 mass%. The composition range is 10 mass% or more and less than 30 mass%, and 0.5 mass% or more and less than 5 mass%.
[0056] The Ni concentration and SiO2 concentration can be measured by ICP emission spectrometry using a solution obtained by dissolving the Zn-Ni-SiO2 composite plating layer.
[0057] There are no particular limitations on the method for coating the surface of the base steel sheet with a Zn-Ni-SiO2 composite plating layer, and any known method can be applied. For example, an electroplating method (Zn-Ni-SiO2 composite electroplating method) can be used.
[0058] In the case of the electroplating method (Zn-Ni-SiO2 composite electroplating method), the Ni concentration and SiO2 concentration of the Zn-Ni-SiO2 composite plating layer can be changed by adjusting the concentrations of Zn, Ni, and SiO2 in the plating bath, and the coverage of the Zn-Ni-SiO2 composite plating layer can be changed by adjusting the electrolysis time.
[0059] The Zn-Ni-SiO2 composite plating layer of the present invention may contain any additive element within a range that does not impair the effects of the present invention. Examples of the optional additive elements include Al, Fe, Co, Mo, V, W, etc.
[0060] As described above, the high-strength steel sheet of the present invention may be a steel sheet having the above-mentioned Zn-Ni-SiO2 composite plating layer coated on one side or both sides of the steel sheet.
[0061] The method for producing the base steel sheet used as the substrate is not particularly limited. In order to facilitate understanding of the present invention, a series of processes from steelmaking in the case where the surface of a cold-rolled steel sheet is coated with a Zn-Ni-SiO2 composite plating layer will be briefly described by way of an example.
[0062] Steel having a predetermined composition is melted and made into a slab by continuous casting according to a conventional method. The obtained slab is then heated in a heating furnace at a temperature of 1100 to 1300°C, hot-rolled at a finishing temperature of 750 to 950°C, and coiled at 500 to 650°C. This is followed by pickling and cold rolling at a rolling reduction of 30 to 70%. Thereafter, according to a conventional method, cleaning treatment is performed by washing with an alkali or a mixed solution of an alkali, a surfactant, and a chelating agent, electrolytic washing, hot water washing, and drying, and then heating treatment is performed at 750 to 900°C and rapid cooling is performed to adjust the tensile strength of the steel sheet. Furthermore, according to a conventional method, temper rolling is performed at an elongation rate of about 0.01 to 0.5% to obtain a cold-rolled steel sheet having a desired tensile strength, and a Zn-Ni-SiO2 composite plating layer is applied to the surface of the cold-rolled steel sheet thus obtained by electroplating to a coating amount of 0.10 g / m 2 The Zn-Ni-SiO2 composite plating layer is coated with the above-mentioned so that the Ni concentration is 2 mass% or more and less than 50 mass%, and the SiO2 concentration is 0.1 mass% or more and less than 10 mass%. This makes it possible to obtain a high-strength cold-rolled steel sheet as an example of the high-strength steel sheet of the present invention.
[0063] When a plating method, particularly an electroplating method, is used to cover the surface of a cold-rolled steel sheet with a Zn-Ni-SiO2 composite plating layer, and there is a risk of hydrogen penetrating into the steel sheet and the Zn-Ni-SiO2 composite plating layer during the plating process, a treatment may be carried out, as necessary, at a temperature of about 100 to 300°C for about 24 hours after the plating process to remove hydrogen that has penetrated into the steel sheet and the Zn-Ni-SiO2 composite plating layer.
[0064] As described above, the high strength steel plate of the present invention is excellent in delayed fracture resistance and corrosion resistance.
[0065] The high strength steel plate of the present invention has excellent delayed fracture resistance and excellent corrosion resistance and can therefore be suitably used for automobile body or suspension parts.
[0066] The high strength steel sheet of the present invention can be suitably used in parts of an automobile body, such as side sills, lower parts of center pillars and bumpers, which require excellent delayed fracture resistance and excellent corrosion resistance.
[0067] Furthermore, since the high strength steel plate of the present invention has excellent delayed fracture resistance and excellent corrosion resistance, it is useful for use in the lower arm portion of an automobile chassis.
[0068] In the present invention, the delayed fracture resistance was evaluated by a corrosion test specified in SAE J2334 shown in Figure 2 using the test piece shown in Figure 1. The details of the test piece and the corrosion test will be described in the Examples. EXAMPLES
[0069] The test pieces used as the base steel sheets were cold-rolled steel sheets (tensile strength 1480 MPa) with a thickness of 1.2 mm and containing each of the component compositions A to G in Table 1. These cold-rolled steel sheets were immersed in toluene and ultrasonically cleaned for 5 minutes to remove the rust-preventive oil, and then Zn-Ni-SiO2 composite electroplating was performed to form a Zn-Ni-SiO2 composite plating layer on the surfaces of both sides of the steel sheets.
[0070] The above tensile strength was measured in accordance with JIS Z 2241 (2011).
[0071] [Table 1]
[0072] The electroplating solution used was one containing divalent zinc ions at a concentration of 65 g / L, divalent nickel ions at a concentration of 10 to 90 g / L as sulfates, 30 g / L of sodium sulfate, and 0 to 20 g / L of SiO2 dispersed therein. The current density was 10 to 80 A / dm 2The Ni concentration and SiO2 concentration of the Zn-Ni-SiO2 composite plating layer were changed by adjusting the electrolysis time within the range, and the coating amount of the Zn-Ni-SiO2 composite plating layer was changed by adjusting the electrolysis time, thereby producing steel sheets No. 1 to 37.
[0073] A steel sheet (No. 38) that was not subjected to the above plating treatment was used as one of the comparative examples.
[0074] The coverage of the Zn-Ni-SiO2 composite plating layer was determined by immersing the steel sheet in hydrochloric acid to dissolve the Zn-Ni-SiO2 composite plating layer, and measuring the difference in mass of the steel sheet before and after dissolution. The end point of dissolution of the Zn-Ni-SiO2 composite plating layer was determined by adding an inhibitor to the hydrochloric acid to prevent iron from dissolving. By adding an inhibitor to the hydrochloric acid, gas is generated while the Zn-Ni-SiO2 composite plating layer is dissolving, but gas generation stops when the dissolution of the Zn-Ni-SiO2 composite plating layer ends. The end of the gas generation was determined by visually observing the end of the gas generation.
[0075] The Ni concentration and SiO2 concentration of the Zn-Ni-SiO2 composite plating layer were measured by dissolving the alloy layer with hydrochloric acid, and the Si concentration was measured by ICP emission spectrometry.
[0076] The test pieces obtained as described above were subjected to the following evaluations. The results are shown in Table 2 together with the composition of the Zn-Ni-SiO2 composite plating layer.
[0077] (1) Evaluation of delayed fracture resistance The test piece (30mm x 99.5mm) prepared by grinding was bent 180° with a radius of curvature of 4mmR, and as shown in Figure 1, this bent test piece 1 was restrained with a bolt 2 and a nut 3 so that the inner interval was 8mm, and the shape of the test piece was fixed, and a test piece for delayed fracture evaluation was obtained. The test piece for delayed fracture evaluation prepared in this way was subjected to a complex cyclic corrosion test in which one cycle (24 hours) was performed in the order of "Step 1: Salt water immersion (15 minutes in a solution containing 0.5 mass% NaCl, 0.1 mass% CaCl2, and 0.075 mass% NaHCO3 at 25°C)", "Step 2: Drying (17 hours and 45 minutes in a 60°C, 50% RH environment)", and "Step 3: Wetting (6 hours in a 50°C, 100% RH environment)" as shown in Figure 2, up to a maximum of 80 cycles. The above one cycle was performed on weekdays (Monday to Friday). On days other than weekdays (Saturday and Sunday), only drying (24 hours in an environment of 60°C and 50% RH) was performed and was not included in the number of cycles performed. Before the salt water immersion process, which was the first process of each cycle, a visual inspection was performed to check for the occurrence of cracks and the number of cycles until cracks occurred was measured. This test was also performed on three specimens of each steel plate, and evaluation was based on the average value. Evaluation was based on the number of cycles and on the following criteria. A test in which the number of cycles until cracks occurred was 30 or more was considered to have passed (○ or △). 〇: 40 or more cycles △: 30 or more cycles, less than 40 cycles ×: Less than 30 cycles
[0078] (2) Evaluation of corrosion resistance The samples that were subjected to the delayed fracture resistance evaluation were visually inspected for the presence or absence of red rust before each cycle of salt water immersion, and the number of cycles for which red rust occurred was measured. Evaluation was based on the number of cycles and was made according to the following criteria. A sample with no red rust occurrence after five cycles was rated as passing (○). ○: No red rust after 5 cycles ×: Red rust occurs within 5 cycles
[0079] [Table 2]
[0080] In Table 2, the number of cycles for crack occurrence for delayed fracture resistance of 40< indicates that cracks occurred at 40 cycles or more, and the number of cycles for corrosion resistance red rust occurrence for corrosion resistance of 30< indicates that red rust occurred at 30 cycles or more.
[0081] According to Table 2, all of the steel sheets of the present invention have excellent delayed fracture resistance and corrosion resistance. In particular, the steel sheets with a coating weight of 20 g / m2 of the Zn-Ni-SiO2 composite plating layer have excellent delayed fracture resistance and corrosion resistance. 2 More than 90g / m 2 It was found that steel sheets Nos. 3 to 7, 11 to 22, 27 to 30, 33, and 34, in which the Ni concentration in the Zn-Ni-SiO2 composite plating layer was 10 mass% or more and less than 30 mass% and the SiO2 concentration was 0.5 mass% or more and less than 5 mass%, obtained excellent corrosion resistance as well as very excellent delayed fracture resistance.
[0082] In contrast, the steel sheets of the comparative examples were inferior in either or both of delayed fracture resistance and corrosion resistance. [Explanation of symbols]
[0083] 1 Test piece 2 Volts 3 Nut
Claims
1. A steel substrate having a tensile strength of 1180 MPa or more and a Zn-Ni-SiO 2 A composite plating layer, The Zn—Ni—SiO 2 The composite plating layer has a coating weight of 20 g / m2 per side. 2 That's all. The Zn—Ni—SiO 2 The Ni concentration in the composite plating layer is 20% by mass or more and less than 30% by mass, The Zn—Ni—SiO 2 SiO in the composite plating layer 2 The concentration is 0.1% by mass or more and less than 10% by mass, and the base steel sheet has a component composition containing, in mass%, C: 0.03% or more and 0.45% or less, Si: 0.01% or more and 3.00% or less, Mn: 0.5% or more and 3.5% or less, P: 0.050% or less, S: 0.0050% or less, Al: 0.001% or more and 1.500% or less, and N: 0.0100% or less, with the balance being Fe and unavoidable impurities.
2. A steel sheet having a tensile strength of 1180 MPa or more, and a Zn-Ni-SiO 2 composite plating layer coated on the surface of the steel sheet. The Zn-Ni-SiO 2 composite plating layer has a coating weight of 20 g / m 2 or more per side, The Ni concentration in the Zn—Ni—SiO 2 composite plating layer is 2 mass% or more and less than 50 mass%, the SiO 2 concentration in the Zn—Ni—SiO 2 composite plating layer is 8.5 mass % or more and less than 10 mass %, and the base steel sheet has a component composition containing, in mass%, C: 0.03% or more and 0.45% or less, Si: 0.01% or more and 3.00% or less, Mn: 0.5% or more and 3.5% or less, P: 0.050% or less, S: 0.0050% or less, Al: 0.001% or more and 1.500% or less, and N: 0.0100% or less, with the balance being Fe and unavoidable impurities.
3. The SiO 2 The high strength steel plate according to claim 1, characterized in that the concentration is 0.5 mass % or more and less than 5 mass %.
4. The SiO 2 The high strength steel plate according to claim 1, characterized in that the concentration is 8.5 mass % or more and less than 10 mass %.
5. The high-strength steel plate according to claim 2, wherein the Ni concentration is 10 mass % or more and less than 30 mass %.
6. The high-strength steel plate according to claim 5, wherein the Ni concentration is 20 mass % or more and less than 30 mass %.
7. The Zn—Ni—SiO 2 The coating weight of the composite plating layer is 90 g / m 2 The high strength steel plate according to any one of claims 1 to 6, characterized in that the strength is less than 100%.
8. The high-strength steel plate according to any one of claims 1 to 7, characterized in that the base steel plate further contains, in mass%, one or more selected from Cu: 1.000% or less, B: 0.0050% or less, Nb: 0.100% or less, Ti: 0.200% or less, V: 0.500% or less, Mo: 1.000% or less, Cr: 1.000% or less, Ni: 1.00% or less, W: 0.200% or less, Zr: 0.200% or less, Hf: 0.200% or less, Co: 0.500% or less, Ca: 0.0050% or less, Mg: 0.0100% or less, Sn: 0.200% or less, Sb: 0.200% or less, and REM: 0.005% or less.
9. An automobile body or suspension part using the high strength steel plate according to any one of claims 1 to 8.
10. 9. An automobile body using the high strength steel sheet according to claim 1 in one or more locations selected from the group consisting of a side sill, a lower part of a center pillar, and a bumper.
11. 9. An automobile chassis using the high strength steel plate according to claim 1 in a lower arm portion.
Citation Information
Patent Citations
High strength galvanized steel sheet excellent in ductility and delayed fracture resistance and its production
JP1994145893A
High strength steel sheet with excellent resistance to hydrogen embrittlement, and its manufacturing method
JP2004231992A
Hot-dip zinc-plated steel sheet and process for production thereof
WO2012081666A1
Zinc-coated steel sheet
WO2021241338A1